"Truth is ever to be found in simplicity, and not in the multiplicity and confusion of things" — Sir Isaac Newton. Issue 2 (6th February 2020) - Smith, Jaclyn A.; Wortley, Mike A.; Bonvini, Sara; Birrell, Mark; Belvisi, Maria G.
We read with interest the recent publication by Morice et al. [1] "The effect of gefapixant, a P2X3 antagonist, on cough reflex sensitivity: a randomised placebo-controlled study" and the accompanying editorial by Turner and Birring [2] "Chronic cough: ATP, afferent pathways and hypersensitivity". The authors of both publications conclude the results are suggestive of two separate neuronal pathways mediating the cough reflex; however, there are significant issues with this interpretation of the data. Over interpretation of cough challenge data only adds to the confusion in our understanding of the mechanisms underlying chronic cough http://bit.ly/2X52CQt